Fabrication of modified hydrogenated castor oil/GPTMS-ZnO composites and effect on UV resistance of leather - Jianzhong Ma (Nature Portfolio, 2017)
Abstract Leather products are made from the natural skin collagen fibers. It is vulnerable to the environmental factor such as solar ultraviolet irradiation in the using process. Therefore anti-UV performance is a very important quality, particularly for chrome-free leather. ZnO is a well-known UV absorber commonly used in the cosmetic industry. We have investigated its potential to increase the anti-UV performance of chrome-free leather. Modified hydrogenated castor oil/GPTMS-ZnO (MHCO/ GPTMS-ZnO) composites were prepared using spherical ZnO nanoparticles, hydrogenated castor oil, maleic anhydride and sodium bisulfite. MHCO/GPTMS-ZnO composites have better anti-UV ability and stability. MHCO/GPTMS-ZnO composites were applied to the leather processing. The treated samples were exposed to artificial sunlight. Anti-yellowing tests showed that MHCO/GPTMS-ZnO composites significantly improved anti-UV performance of leather.